Investigation of the Reduction of Graphene Oxide by Lithium Triethylborohydride. (11th January 2016) - Xu, Guangyuan; Malmström, Jenny; Edmonds, Neil; Broderick, Neil; Travas-Sejdic, Jadranka; Jin, Jianyong
Abstract : The chemical reduction of a wet colloidal suspension of graphene oxide is a cost-effective and adaptable method for large scale production of "quasi" graphene for a wide variety of optoelectronic applications. In this study, modified Hummers' procedure was used to synthesize high quality graphene oxide at 50°C. This modified protocol thus eliminates the potentially hazardous second high-temperature step in Hummers' method for the production of GO. Furthermore, the reduction of graphene oxide by lithium triethylborohydride is demonstrated for the first time. According to FT-IR, UV-Vis, TGA, Raman, SEM/EDS, and AFM results, the reduced graphene oxide (LiEt3 BH-RGO) has properties comparable to other reduced graphene oxide products reported in the literature.